PENERAPAN PEMROSESAN PARALEL UNTUK MENGUJI WAKTU RENDERING DESIGN WEB DENGAN FRAMEWORK TERHADAP PROCESSOR MELALUI LAN, ROUTER DAN EKSTRANET - Ngadiyono Ngadiyono; Hero Wintolo (Compiler, 2015)
Designing a website is the first step to build website that gives the appearance of an interface to the website visitor. the appearence web design that interesting can be gived conveniences for visitors to browse the contents of any website content. designing of the website, skill are required several to be master multiple web programming languages, the programming language are  HTML, CSS and Javascript. In the overall control of the programming language takes time to be master and understand each other codes. Therefore, to built application that allows users to create a website design. This application is called WebEditor is built using CodeIgniter and Twitter Bootstrap framework. In the rendering process design needed parallel processing techniques to the process. so, the impact in terms of rendering time speed to website design. Throughout this system, users can design a website easily and quickly, and in the process of rendering design does not require for long time. the results of study case have done that it can be seen that influences of the implementation of rendering speed transmission media based on the number of processors and computers server. The percentage of the speed to rendering of design does not using a grid server on the LAN network are 33.7 %, 33.3 % and internet routers 33 %. While using a part of grid servers on the LAN network are 33.6 %, 33.4 % and internet routers 33 % and the final grid using 2 servers on the LAN network are 44 %, 33 % and internet routers 26 %. So the highest rendering speed on the LAN router network for further 44 % and 30 % at the latest on the Internet 26 % by using 2 part of grid servers. Thus rendering the best in the website design is using LAN with 2 part of grid servers.